Health-related quality of life in children with juvenile idiopathic arthritis: A developing country perspective - Madhumita Nandi; Abhisek Majhi; Moumita Samanta; Tanmoy Sar; Sumantra Sarkar; Tapas Sabui (Indian Journal of Rheumatology)
Objective: To assess the Health-Related Quality of Life (HRQoL) in domains of physical, emotional, social, and school functioning in children suffering from juvenile idiopathic arthritis (JIA). Materials and Methods: This hospital-based prospective observational study was undertaken in children from 2 to 12 years of age attending the Rheumatology clinic of a tertiary care teaching institute of Eastern India with a diagnosis of JIA for at least 6 months. Pediatric QoL inventory 4.0 generic core scale was used after obtaining the necessary permission. Results: Out of a total of 92 patients of JIA, 85 (male/female: 39/46) were taken up for the study polyarticular JIA was the commonest variety (54/85, 63.5%) followed by systemic JIA (sJIA) (25/85, 29.4%) and oligoarticular JIA (6/85, 7.0%). Male gender (P = 0.059, 0.000), better BMI (P = 0.004, 0.001), better disease control (P = 0.00, 0.00), sJIA subcategory (P = 0.002, 0.000), and longer duration of disease (P = 0.015, 0.000) correlated with better QoL in both child and parent scores whereas better socioeconomic status fared better only in parent scores (P = 0.017) and educational status of parents in child scores (child P = 0.000), Child and parent score were comparable across all domains and also overall scores. Conclusion: This study brings out certain important aspects of QoL in children suffering from JIA which may have some significant impact on disease control per se. Larger community-based multicentric studies would help us in delineating further this aspect of the disease and formulating guidelines for improving QoL in such children.